Perception of the necessity of orthodontics treatment by adolescents and their parents - Josefa Navarro Nápoles; Manuela Ricardo Reyes; Maira Raquel Martínez Ramos; Manuel Alejandro López Díaz; Norayda Cobas Pérez (Centro Provincial de Información de Ciencias Médicas, 2018)
An epidemiologic, observational, descriptive and cross-sectional study, of 136 scholars aged 12 to 14, of "Antonio Maceo Grajales" Urban Secondary School was carried out in Santiago de Cuba, from September, 2015 to February, 2016, aimed at determining, in these and in their parents, the perception of the necessity of orthodontic treatment through the index of dental cosmetic.  Among the main results of the series a higher frequency of dental crowding was obtained (69.1%) as component of the Index and a prevalence of the minor malocclusion (no need of treatment), with 53.7%, followed by the defined malocclusion (elective therapy), with 28.7%.  It was concluded that most of the parents were satisfied with the dental occlusion of their children and that a high number of the scholars was happy with their dental cosmetic.